Pembentukan Karakter Bangsa Melalui Paradigma Pendidikan - Isfihani, Isfihani (Al-Riwayah : Jurnal Kependidikan, 2017)
Character comes from the Latin word chiseled. However, it differs from the Greek, which means Karasso blueprint, the basic format prints, such as the fingerprint. This terminology usually refers to an idealist-spiritualist approach in education, it’s known as normative educational theory. The priorities are transcendent values as the motor of history, both for individuals and for social change. National Education Act states clearly that a noble character is an important aspect in educating children. Even the character of a nation is determined by the character of his people. In addition, Formation of character would be attempt to the shape of character. Character education is the provision of views on various values of life, such as honesty, intelligence, caring, responsibility, truth, beauty, goodness, and faith. Thus, character-based education can integrate information obtained during the study to be a way of life that is useful for reduction of life issue. Character-based education will demonstrate its identity as a self-conscious human beings, human beings and citizens.